2019
DOI: 10.1007/s00404-019-05340-4
|View full text |Cite|
|
Sign up to set email alerts
|

A multicenter, double-blind, randomized trial on the bleeding profile of a drospirenone-only pill 4 mg over nine cycles in comparison with desogestrel 0.075 mg

Abstract: Purpose A typical compliance problem in the use of traditional progestin-only pills is the irregular bleeding pattern and the strict daily intake. Desogestrel 75 mg has a 12-h missed-pill window; however, its poor cycle control limits a more common use. Methods A drospirenone (DRSP)-only pill was developed to improve the bleeding profile. Setting A phase III study in healthy women aged 18–45 years was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…Bleeding pattern: control of bleeding profile with 4 mg DRSP in comparison to 75 µg desogestrel. A phase III clinical trial over 9 administration cycles compared bleeding profiles of women treated with 4 mg DRSP and women treated with 75 µg desogestrel [46,47]. The percentage of women with bleeding and spotting decreased in the 4 mg DRSP group from 69.2 % in administration cycle 2 to 56.3 % in administration cycle 9, and in the 75 µg desogestrel group from 74.05 % to 45.3 %.…”
Section: Tolerancementioning
confidence: 99%
“…Bleeding pattern: control of bleeding profile with 4 mg DRSP in comparison to 75 µg desogestrel. A phase III clinical trial over 9 administration cycles compared bleeding profiles of women treated with 4 mg DRSP and women treated with 75 µg desogestrel [46,47]. The percentage of women with bleeding and spotting decreased in the 4 mg DRSP group from 69.2 % in administration cycle 2 to 56.3 % in administration cycle 9, and in the 75 µg desogestrel group from 74.05 % to 45.3 %.…”
Section: Tolerancementioning
confidence: 99%
“…Moreover, the rate of patients with prolonged bleeding (>10 days) was significantly lower in the 4 mg drospirenone group compared with the 75 lg desogestrel group for cycles 5-9 (p < 0.001). Early study withdrawal related to abnormal uterine bleeding (AUB) was reported for 3.3% of participants who received 4 mg drospirenone against 6.6% who took 75 lg desogestrel (p < 0.001) [27]. The results demonstrated that cycle control with 4 mg drospirenone was superior to that with 75 lg desogestrel.…”
Section: Tolerabilitymentioning
confidence: 98%
“…A comparison of cycle control between 4 mg drospirenone and 75 lg desogestrel was performed in a study of nine cycles [27]. The proportion of women with bleeding and spotting decreased from 69.7% in cycle 2 to 56.3% in cycle 9 in the 4 mg drospirenone group and from 74.0% to 45.3% in the 75 lg desogestrel group; the overall median number of bleeding and spotting days decreased from 10 days (first reference period: cycles 2-4) to 6 days (last reference period: cycles 7-9) in the 4 mg drospirenone group and from 12 to 7 days in the 75 lg desogestrel group.…”
Section: Tolerabilitymentioning
confidence: 99%
“…The most recent novel introduction of a high dose progestin only pill is the 4 mg drosperinone oral contraceptive pill that provides a progestin-only option with good bleeding control. This pill also allows a non-time-restricted daily intake, very different from low-dose POP options [ 4 ].…”
Section: A Brief History Of the Tight Interlink Between Products Desimentioning
confidence: 99%
“…The 4 pill free days are designed allow a controlled withdrawal bleeding episode [compared to the 28-day minipill regimen with no window for bleeding]. This high dose drosperinone oral contraceptive pill provides a progestin-only option with good bleeding control without the restricted daily intake 2–3 h time frame [ 4 ].…”
Section: Low-dose Progestin-only Pills Often Have Poor Bleeding Contrmentioning
confidence: 99%